2001
DOI: 10.1021/jp004466f
|View full text |Cite
|
Sign up to set email alerts
|

Size-Selected Nanoparticle Chemistry:  Kinetics of Soot Oxidation

Abstract: A new experimental method has been developed to conduct surface chemistry and extract surface kinetic rates on size-selected nanoparticles. The method utilizes a tandem differential mobility analyzer (TDMA) technique in which monodisperse particles are selected from a polydisperse aerosol input stream and then subjected to chemical processing. The change in particle size is measured and used to determine kinetic information for the relevant surface reaction. The method has been applied to measure the oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
169
1
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(185 citation statements)
references
References 42 publications
11
169
1
1
Order By: Relevance
“…Figure 8 shows an Arrhenius plot of oxidation rates for this study in comparison with results obtained in other studies, which have been shown in Higgins et al (2002Higgins et al ( , 2003. In order to keep the results comparable, a hypothesis of 120 m 2 /g surface area of particle samples was used to calculate the surface-specific oxidation from the mass decrease rate, following the same approach in Higgins et al (2002Higgins et al ( , 2003. For pure biodiesel soot, Jung et al (2006) reported an activation energy of 89 kJ/mol (line c), which is lower than results obtained in this study.…”
Section: Particle Oxidationsupporting
confidence: 64%
See 3 more Smart Citations
“…Figure 8 shows an Arrhenius plot of oxidation rates for this study in comparison with results obtained in other studies, which have been shown in Higgins et al (2002Higgins et al ( , 2003. In order to keep the results comparable, a hypothesis of 120 m 2 /g surface area of particle samples was used to calculate the surface-specific oxidation from the mass decrease rate, following the same approach in Higgins et al (2002Higgins et al ( , 2003. For pure biodiesel soot, Jung et al (2006) reported an activation energy of 89 kJ/mol (line c), which is lower than results obtained in this study.…”
Section: Particle Oxidationsupporting
confidence: 64%
“…For diesel soot, the following reported lower activation energy than those obtained in this study : Jung et al (2005) with 25 ppm cerium-dosed case (line a, 107 kJ/mol); Jung et al (2003) with lube-oil-dosed case (line b, 101 kJ/mol); Higgins et al (2003) with regular diesel fuel (line e, 108 kJ/mol); Ahlström and Odenbrand (1989) with flow reactor study of diesel particles (line h, 106 kJ/mol). On the other hand, Miyamoto et al (1988) obtained higher results using TGA for uncatalyzed diesel soot (line f, 191 kJ/mol) and the following two obtained similar results: Higgins et al (2002) using diffusing flame-generated soot (line d, 164 kJ/mol) and Otto et al (1980) using TGA for diesel particles (142 kJ/mol). Clearly, the activation energy depends on the type of fuel, the treatment of the fuel or the soot, and the methods of measurement.…”
Section: Particle Oxidationmentioning
confidence: 73%
See 2 more Smart Citations
“…Several studies have been conducted to understand the kinetics of soot oxidation. Higgins et al 53 derived an expression for the kinetics of the oxidation of diesel soot particles as a function of size. Particle size was measured for selected monodispersed particle populations with a TDMA before and after oxidation at high temperature.…”
Section: Kinetics Of Oxidationmentioning
confidence: 99%